The Influence of Foreign Investment, Domestic Investment, and District Minimum Wages on Regional Original Income in Bali Province - Bagas Nurdianto; Wenny Restikasari (PT FORMOSA CENDEKIA GLOBAL, 2026)
This study aims to analyze the effect of Foreign Direct Investment (FDI), Domestic Investment (DI), and Regency/Municipal Minimum Wages on Regional Original Revenue (ROR) in Bali Province. ROR is an important indicator of regional fiscal independence, which is influenced by various economic factors, particularly investment and labor market conditions. This study uses secondary data consisting of FDI, DI, minimum wages, and ROR across regencies/municipalities in Bali Province during the period 2020–2024, obtained from the Central Bureau of Statistics and relevant institutions. The analytical method employed is panel data regression using the Fixed Effect Model (FEM), which was selected based on the Chow test and Hausman test results. The findings indicate that, partially, FDI and minimum wages have a positive and significant effect on ROR, while domestic investment does not have a significant effect. Simultaneously, FDI, domestic investment, and minimum wages significantly affect Regional Original Revenue in Bali Province. These results suggest that foreign investment and wage policies play an important role in strengthening regional fiscal capacity through increased economic activity and purchasing power. Therefore, local governments are expected to promote a conducive environment for foreign investment and implement balanced wage policies to sustainably enhance Regional Original Revenue.